Gift of the Hungarian Queen from Kyiv: Sword as a Metaphor - Radvan, Dana (Studia Philologica, 2024)
The article will analyze records in chronicles about usage of sword in medieval Rus’ in metaphorical context. Facts provided in the Tale of Bygone Years and the Radziwiłł Chronicle will be interpreted in connection with the record of Lampert of Hersfeld about the gift of the Attila’s sword, made by the Hungarian Queen Anastasia to Otto, Duke of Bavaria, in the second half of the 11th century, in order to interpret metaphorical meanings conveyed with the help of sword and explain the unusual ceremonial choice of the Hungarian Queen in view of her origin from Kyiv.